Stability and G × E analysis of zinc-biofortified rice genotypes evaluated in diverse environments - Inabangan-Asilo, Mary Ann; Swamy, B.P. Mallikarjuna; Amparado, Amery F.; Descalsota-Empleo, Gwen Iris L.; Arocena, Emily C.; Reinke, Russell (Springer, 2019)
Rice is the major staple food and source of energy in Asia, particularly in the Philippines. Most of the popular, high-yielding rice varieties lack sufficient amount of micronutrients to meet daily human requirements. Micronutrient deficiencies are a major health burden globally and can cause severe health problems. In the Philippines, nearly one-third of the population is zinc (Zn) deficient. Breeding healthier rice varieties is one of the major sustainable interventions to tackle micronutrient deficiencies. However, genotype and environment interactions (G × E) are a major obstacle in breeding for high-Zn rice varieties, thus an understanding of G × E interactions and identifying stable genotypes through multi-location evaluation will help in identifying potential lines for varietal release. We evaluated eight high-Zn rice breeding lines along with checks in several locations across the Philippines during 2014 wet season (WS), 2015 dry season (DS) and 2015WS, and 2016DS. Individual and combined analysis of variance revealed significant genotypic effects and G × E interactions for all the traits studied. Significant positive correlations between grain iron (Fe) and Zn, days to maturity, and plant height were observed, whereas grain yield and Zn were negatively correlated. Stability analysis using Kang’s stability index, additive main effects and multiplicative interaction, and genotype main effects plus G × E (GGE) consistently identified IR10M300 as the most stable genotype across seasons in terms of yield and grain Zn. Over all IR10M300 has a yield of 4690.3 kg ha−1 and grain Zn of 18.3 ppm. It outperformed two rice variety checks (PSBRc82 and MS13) for grain Zn with comparable yield with the yield check (PSBRc82) and was successfully released as the first High-Zinc Rice 1 (NSICRc 460) in the Philippines.